Mineral Content in Different Banana Varieties of Bangladesh - Ema, Farhana Kabir; Barua, Sagarmay; Islam, SK Nazrul (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.95-98